Penyuluhan Edukasi Tentang Kesadaran Mahasiswa Dalam Beretika Prodi MIK STIKes Santa Elisabeth Medan - Pomarida Simbolon; Bernad Julvian Zebua; Ita Monita Munthe; Jetslin Simbolon; Lea Sri Ita; Scere Sophia Sitorus (Lembaga Pengembangan Kinerja Dosen, 2024)
Awareness is a condition where a person understands the rights and obligations that he must carry out. Someone who is aware and understands will definitely carry out their responsibilities seriously (Muldiah, 2023). Studentship also comes from the sub-word student, while student is further divided into two syllables, namely maha and student. Maha means